2020
DOI: 10.1002/aenm.202000363
|View full text |Cite
|
Sign up to set email alerts
|

Double the Capacity of Manganese Spinel for Lithium‐Ion Storage by Suppression of Cooperative Jahn–Teller Distortion

Abstract: The relatively low capacity and capacity fade of spinel LiMn2O4 (LMO) limit its application as a cathode material for lithium‐ion batteries. Extending the potential window of LMO below 3 V to access double capacity would be fantastic but hard to be realized, as it will lead to fast capacity loss due to the serious Jahn–Teller distortion. Here using experiments combined with extensive ab initio calculations, it is proved that there is a cooperative effect among individual Jahn–Teller distortions of Mn3+O6 octah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(63 citation statements)
references
References 43 publications
1
62
0
Order By: Relevance
“…This leads to the distinct evolution of voltage regions near 4 V and 3 V, [64,65] similar to what was observed on metastable DRX materials such as Li 4 Mn 2 O 5 . [66][67][68] The arrangements not only create excellent percolation pathways of low activation energy Li migration channels [69][70][71] but also mitigate Jahn-teller distortion and enhance structural stability, [63,72] leading to better material utilization at a given current density, increased accessible capacity and more than 100% of capacity retention with cycling. It is conceivable that over-lithiation of the off-stoichiometry spinel-like domains occurs upon discharging below 3 V, enabling additional capacity not accounted in the pristine material and contributing to additional discharge capacity.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to the distinct evolution of voltage regions near 4 V and 3 V, [64,65] similar to what was observed on metastable DRX materials such as Li 4 Mn 2 O 5 . [66][67][68] The arrangements not only create excellent percolation pathways of low activation energy Li migration channels [69][70][71] but also mitigate Jahn-teller distortion and enhance structural stability, [63,72] leading to better material utilization at a given current density, increased accessible capacity and more than 100% of capacity retention with cycling. It is conceivable that over-lithiation of the off-stoichiometry spinel-like domains occurs upon discharging below 3 V, enabling additional capacity not accounted in the pristine material and contributing to additional discharge capacity.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] revealed that the 16 d sites in the spinel LNMO can be partially occupied by Ti 4+ , providing longer cycle life. One further work [ 24 ] on the LiMn 2 O 4 cathode, which is isostructural to LNMO, shows that the substitution of Mn with Li at 16 d sites in the LiMn 2 O 4 material significantly suppresses the cooperative Jahn–Teller effects as a result of the increased cationic disorder. Considering the similarity between LNMO and LiMn 2 O 4 structures, this further supports the strategy to target 16 d sites to reduce Mn dissolution in high‐voltage LNMO.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that the higher Mn 4+ /Mn 3+ ratio (5 in our case) suggests structural stability. [34][35][36] Therefore, the Mn 4+ LiMn 2 O 4 spinel. For this reason, the stronger bonds of the octahedron MO 6 can be prevented from dissolving Mn, maintains structural stability, and allows a higher Li + diffusion during the electrochemical cycle, so that the cycling stability and the velocity capacity of our sample are improved.…”
Section: Phase Identification Resultsmentioning
confidence: 99%